Roller-cam systems design: development of a profile analysis software (2009)
The different options involved in cam systems design such as types of cams and followers, number of applicable standard cam functions, divisions of follower motion-segments, and possible combinations of follower displacement profiles, among others, were critically studied to determine the structure and capabilities of a software package suited for extensive design analyses. The software was applied in the design of cam profiles with selected follower and cam functions and the results obtained were found comparable with those obtained from numerical methods and existing software packages.